Detection of Antibiotics Residue in Chicken Meat Using TLC - Tajick, M.A.; Shohreh, B. (International Journal of Poultry Science, 2006)
Nowadays antibiotics are applying for control of infectious diseases in chickens digestive system. Incorrect use of this drugs deposits some residue in product. This research highlights the importance and existence of antibiotics residue in meat. In this survey 10 grams of chicken meat crashed and squeezed in 10 ml ethanol. After clarifying by centrifuge the solvent evaporated totally. After loading and running on silica F256 plates, the chromatograms observed on UV light. The results showed more than 50% of meat samples had noticeable antibiotics residue.